Ketamine, but Not the NMDAR Antagonist Lanicemine, Increases Prefrontal Global Connectivity in Depressed Patients. (August 2018) - Abdallah, Chadi G.; Dutta, Arpan; Averill, Christopher L.; McKie, Shane; Akiki, Teddy J.; Averill, Lynnette A.; William Deakin, J. F.
Background: Identifying the neural correlates of ketamine treatment may facilitate and expedite the development of novel, robust, and safe rapid-acting antidepressants. Prefrontal cortex (PFC) global brain connectivity with global signal regression (GBCr) was recently identified as a putative biomarker of major depressive disorder. Accumulating evidence have repeatedly shown reduced PFC GBCr in major depressive disorder, an abnormality that appears to normalize following ketamine treatment. Methods: Fifty-six unmedicated participants with major depressive disorder were randomized to intravenous placebo (normal saline; n = 18), ketamine (0.5 mg/kg; n = 19), or lanicemine (100 mg; n = 19). PFC GBCr was computed using time series from functional magnetic resonance imaging scans that were completed at baseline, during infusion, and at 24-h posttreatment. Results: Compared to placebo, ketamine significantly increased average PFC GBCr during infusion ( p  = 0.01) and at 24-h posttreatment ( p  = 0.02). Lanicemine had no significant effects on GBCr during infusion ( p  = 0.45) and at 24-h posttreatment ( p  = 0.23) compared to placebo. Average delta PFC GBCr (during minus baseline) showed a pattern of positively predicting depression improvement in participants receiving ketamine ( r  = 0.44; p  = 0.06; d  = 1.0) or lanicemine ( r  = 0.55; p  = 0.01; d  = 1.3) but not those receiving placebo ( r  = −0.1; p  = 0.69; d  = 0.02). Follow-up vertex-wise analyses showed ketamine-induced GBCr increases in the dorsolateral, dorsomedial, and frontomedial PFC during infusion and in the dorsolateral and dorsomedial PFC at 24-h posttreatment ( corrected p  < 0.05). Exploratory vertex-wise analyses examining the relationship with depression improvement showed positive correlation with GBCr in the dorsal PFC during infusion and at 24-h posttreatment but negative correlation with GBCr in the ventral PFC during infusion ( uncorrected p  < 0.01). Conclusions: In a randomized placebo-controlled approach, the results provide the first evidence in major depressive disorder of ketamine-induced increases in PFC GBCr during infusion and suggest that ketamine's rapid-acting antidepressant properties are related to its acute effects on prefrontal connectivity. Overall, the study findings underscore the similarity and differences between ketamine and another N-methyl-D-aspartate receptor antagonist while proposing a pharmacoimaging paradigm for the optimization of novel rapid-acting antidepressants prior to testing in costly clinical trials.